DEBUNKING THE POST-RACIAL NOTION: A RACIAL PREJUDICE STUDY IN AMERICAN SOCIETY AS REFLECTED IN ANGIE THOMAS’ THE HATE U GIVE - Yusrina Dinar Prihatika; Muh Arif Rokhman (Rubikon : Journal of Transnational American Studies, 2020)
Today, America is still busy with the problems of inequality, which include racial prejudice.The Hate U Give brings social issues that are rife to people of color, especially African Americans. In her novel, Thomas illustrates the injustice that had happened to the African American community because of the racial profiling that was carried out by white people. The writer uses descriptive analysis method in finding the meaning behind a literary work. The writer also conducts the study using Racial Prejudice theory by McLemore to see the types of prejudice in society. The writer also elaborates it with Du Bois’ Double Consciousness in analyzing racial prejudice towards African Americans. The study found out that perceived injustice is still often obtained by African Americans, where they still cannot have their rights as citizens in the United States, such as educational equality, economics, and legal protection. This prejudice is caused by the existence of social class conditions which are constrained by the majority race which tries to maintain its position as a 'ruler' in American society, the other factor is by the spreading Post-Racial ideology where the majority of people think that talking about racial issues is no longer relevant.